2017
DOI: 10.4067/s0717-97072017000303653
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Bioavailability and Bioaccessibility of Total Arsenic and Arsenic Species in Environmental Samples

Abstract: Studies on the bioavailability of As, of impacted vegetables; and As bioaccesibility in the edible parts of carrots (daucus carota), beets (beta vulgaris) and quinoa (chenopodium) growing in polluted soils thought "in vitro" gastrointestinal process; the As speciation both in the edible parts of vegetables and in their gastrointestinal extracts have been performed. Elemental analysis and As speciation have been performed by ICP-MS and LC-ICP-MS, respectively. The Arsenic recovery after the in vitro gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…In vitro methods are designed to simulate the pH of the fasting state in a young child, and these conditions have been found to lead to higher bioaccessibility values for many metal (loid)s and thus are considered a more conservative approach (Moreda-Piñeiro et al, 2011). By using a PBET-based approach, Pizarro et al (2017) found that the bioaccessibility value of As for quinoa (Chenopodium quinoa Willd.) was around 40% while those in carrots (Daucus carota subsp.…”
Section: Occurrence and Bioavailability Of Arsenic In Edible Crops An...mentioning
confidence: 99%
“…In vitro methods are designed to simulate the pH of the fasting state in a young child, and these conditions have been found to lead to higher bioaccessibility values for many metal (loid)s and thus are considered a more conservative approach (Moreda-Piñeiro et al, 2011). By using a PBET-based approach, Pizarro et al (2017) found that the bioaccessibility value of As for quinoa (Chenopodium quinoa Willd.) was around 40% while those in carrots (Daucus carota subsp.…”
Section: Occurrence and Bioavailability Of Arsenic In Edible Crops An...mentioning
confidence: 99%